Phosphine‐Catalyzed (3+2) Annulation of Isoindigos with Allenes: Enantioselective Formation of Two Vicinal Quaternary Stereogenic Centers. (27th February 2019) - Chan, Wai‐Lun; Tang, Xiaodong; Zhang, Fuhao; Quek, Glenn; Mei, Guang‐Jian; Lu, Yixin
Abstract: Construction of contiguous all‐carbon quaternary stereogenic centers is a long‐standing challenge in synthetic organic chemistry. In this report, a phosphine‐catalyzed enantioselective (3+2) annulation reaction between allenes and isoindigos, containing either two identical or different oxindole moieties, is introduced as a powerful strategy for the construction of spirocyclic bisindoline alkaloid core structures. The reported reactions feature high chemical yields, excellent enantioselectivities, and very good regioselectivities, and are highly useful for creating structurally challenging bisindoline natural products. Abstract : Strategischer Zug : Die phosphinkatalysierte enantioselektive (3+2)‐Anellierung zwischen Allenen und Isoindigos wird als eine leistungsfähige Strategie für den Aufbau von Strukturmotiven mit zwei vicinalen quartären stereogenen Zentren vorgestellt. Die Reaktionen zeichnen sich durch hohe Ausbeuten, Enantioselektivitäten und Regiolektivitäten aus und sind sehr nützlich für die Herstellung von strukturell anspruchsvollen Hexahydropyrroloindolen (HPIs).